Strengthening mechanisms of two-stage evaporation strategy on system performance for organic Rankine cycle. (15th April 2016) - Li, Tailu; Yuan, Zhenhe; Li, Wei; Yang, Junlan; Zhu, Jialing
Abstract: The ORC (organic Rankine cycle) technology has been found promising for heat recovery, but the major problem is its low efficiency, and the evaporator is a major contributor to the total irreversible losses. The heat source is segmented in two temperature ranges. The TSORC (two stage organic Rankine cycle) was put forward. The objective of this paper is to evaluate the performance enhancement of the TSORC with a reference to the ORC. The system performances (mass flow rate, evaporating temperature, VFR (volumetric flow ratio), net power output, system efficiency, and thermal conductances) for the ORC and TSORC were simulated and compared using R245fa. The objective function is the ratio of the net power output to the total thermal conductance, reflecting both the system earnings and the cost. The results show that the TSORC can enhance the net power output, and the growth rate differs with IGWT (intermediate geothermal water temperature) and GWIT (geothermal water inlet temperature) (GWIT). The TSORC exceeds the ORC and enhances the systematic performance with the GWIT. Optimal IGWT and evaporating temperatures of the TSORC maximize the net power output. The TSORC presents excellent systematic performance, which should be popularized in engineering applications. Highlights: Two-stage evaporation is feasible for the ORC. Two-stage evaporation evidently increases system performance. The TSORC tends to improve the performance of ORC. The TSORC is more preferable than the ORC.